Impact of a Pharmacist-included Mobile Geriatrics team intervention on potentially inappropriate drug prescribing: protocol for a prospective feasibility study (PharMoG study). Issue 12 (2nd December 2020) - Pagès, Arnaud; Roland, Christel; Qassemi, Soraya; Abdeljalil, Anne-Bahia; Houles, Mathieu; Romain, Marjolaine; Toulza, Olivier; Belloc, Audrey; McCambridge, Cécile; Voisin, Thierry; Cestac, Philippe; Juillard-Condat, Blandine
Abstract : Introduction: Research has shown that potentially inappropriate drug prescription (PIDP) is highly prevalent in older people. The presence of PIDPs is associated with adverse health outcomes. This study aims to evaluate the impact of a PHARmacist-included MObile Geriatrics (PharMoG) team intervention on PIDPs in older patients hospitalised in the medical, surgical and emergency departments of a university hospital. Methods and analysis: The PharMoG study is a prospective, interventional, single-centre feasibility study describing the impact of a PharMoG team on PIDPs in older hospitalised patients. Pharmacist intervention will be a treatment optimisation (clinical medication review) based on a combination of explicit and implicit criteria to detect PIDPs. The primary outcome is the acceptance rate of the mobile team's proposed treatment optimisations related to PIDPs, measured at the patient's discharge from the department. This pharmacist will work in cooperation with the physician of the mobile geriatric team. After the intervention of the mobile geriatric team, the proposals for improving therapy will be sent to the hospital medical team caring for the patient and to the patient's attending physician. The patient will be followed for 3 months after discharge from the hospital. Ethics and dissemination: This study was approved by the South-West and Overseas Territories II Ethics Committee. Oral consent must be obtained prior to participation, either from the patient or from the patient's representative (trusted person and/or a family member). The results will be presented at national and international conferences and published in peer-reviewed journals. Trial registration number: NCT04151797 .